Analysis and research on the constant-rate penetration mechanism of the seabed cone penetration test system - Ren, Ziqiang; Chen, Jiawang; Guo, Jin; Liu, Bijin; Hu, Xiaohui; Zhou, Hang; Liu, Houhong; Gao, Feng (Frontiers in Mechanical Engineering, 2023)
The seabed Cone Penetration Test (CPT) system is a common method for investigating offshore soil. This paper focuses on a new subsea CPT method for assessing physical and mechanical properties of marine sediments. The new method enables automatic docking and dismantling of the probe rods underwater. The constant-rate penetration mechanism is the basis and core component of the seabed CPT, allowing the probe rod and cone to penetrate the seafloor sediment. Double hydraulic cylinders are used to meet the high penetration force requirements. To maintain a constant penetration rate of 20 ± 5 mm/s, the model identification of the electro-hydraulic servo system is performed using Simcenter AMESim and MATLAB software, and the relevant transfer function is obtained using the PID method. Based on this transfer function, the sliding mode variable structure controller of the electro-hydraulic servo system is designed to regulate the constant penetration rate of the hydraulic cylinder against varying penetration resistance. Simulation results demonstrate the accuracy and applicability of the control system for the hydraulic penetration mechanism. In-situ measurements using the new seabed CPT rig in Zhoushan Island confirm that the sliding mode variable structure controller is suitable for controlling the system during actual operation.